Pharmacological Influencing of The Cholinergic Anti-inflammatory Pathway in Infectious Diseases and Inflammatory Pathologies - Pohanka, Miroslav (Mini Reviews in Medicinal Chemistry, 2021)
The cholinergic anti-inflammatory pathway is a part of the parasympathetic nervous system and it can also be entitled as an anti-inflammatory reflex. It consists of terminations of the vagal nerve into blood, acetylcholine released from the terminations, macrophages and other cells having α7 nicotinic acetylcholine receptor (α7 nAChR), calcium ions crossing through the receptor and interacting with nuclear factors, and erythrocytes with acetylcholinesterase (AChE) terminating the neurotransmission. Stopping of inflammatory cytokines production is the major task for the cholinergic antiinflammatory pathway. The cholinergic anti-inflammatory pathway can be stimulated or suppressed by agonizing or antagonizing α7 nAChR or by inhibition of AChE. This review is focused on cholinergic anti-inflammatory pathway regulation by drugs. Compounds that inhibit cholinesterases (for instance, huperzine, rivastigmine, galantamine), and their impact on the cholinergic anti-inflammatory pathway are discussed here and a survey of actual literature is provided.
Keywords: acetylcholine receptor